Employability skills towards the employment readiness among FPA undergraduate students / Nurulhuda Mansor - Mansor, Nurulhuda (Faculty of Plantation and Agrotechnology, 2019)
Employability skills is crucial in the workplace to ensure the performance of employee as well as improving company performance. Employer have rated the employability skills as highly important as a determinant for a graduate to secure a job. The objectives of this research is to identify the employability skills possess by students as well as to identify the most dominant skills of Faculty of Plantation and Agrotechnology undergraduate students. Information provided can be a guideline for those who wants to further studies regarding employability skills of FPA undergraduates. FPA may find this research useful to develop module or training in effort to improve skills of FPA students. The research focus on the students of FPA at Universiti Teknologi MARA Melaka Kampus Jasin. The respondent are the final year students of diploma and degree program of FPA. The sample sizes are calculated using sample size calculator by Raosoft Incorporation. Data collected using questionnaires are then analyse using Statistical Package for the Social Science (SPSS) software version 22. The results show that students’ dominant skill is cooperation and the lowest skill possession is decision making. Most of the students recognized that the employability skills help in enhancing employment readiness. The issue of graduates’ unemployment is a problem for educational institutions, employer and the nation. Hence, the collaboration of all parties will help in overcoming this problem.